2019
DOI: 10.1001/jamadermatol.2018.3970
|View full text |Cite
|
Sign up to set email alerts
|

α-Gal Syndrome vs Chronic Urticaria

Abstract: Galactose-α-1,3-galactose (α-gal) is an oligosaccharide expressed on glycoproteins and glycolipids of nonprimate mammals and is the causal epitope of an IgE-mediated allergy to mammalian meat. 1,2 First reported in 2009, the α-gal syndrome is an increasingly appreciated problem across the southeastern United States and other parts of the world. 2 It is clear that tick bites, specifically relating to Amblyomma americanum (lone star tick), are causal in many, if not most, cases of α-gal sensitization in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…It is suggested that inactivated SARS-CoV-2 whole virus could serve as effective multiantigenic vaccine if it is glycoengineered to present multiple α-gal epitopes in order to achieve anti-Gal mediated targeting to APC for extensive uptake of the vaccinating virus by these cells. Since few individuals produce anti-Gal IgE causing meat allergy to α-gal epitopes in beef, pork and lamb ("α-gal syndrome") [18,19], those with this syndrome should receive vaccines presenting α-gal epitopes in clinics equipped for treating allergic reactions. Vaccinating SARS-CoV-2 α-gal binds the natural anti-Gal antibody at the vaccination site and activates the complement system to generate complement cleavage chemotactic peptides that recruit APC such as dendritic cells and macrophages.…”
Section: Covid-19 Variants As Moving Targets and How To Stop Them By Glycoengineered Whole-virus Vaccinesmentioning
confidence: 99%
“…It is suggested that inactivated SARS-CoV-2 whole virus could serve as effective multiantigenic vaccine if it is glycoengineered to present multiple α-gal epitopes in order to achieve anti-Gal mediated targeting to APC for extensive uptake of the vaccinating virus by these cells. Since few individuals produce anti-Gal IgE causing meat allergy to α-gal epitopes in beef, pork and lamb ("α-gal syndrome") [18,19], those with this syndrome should receive vaccines presenting α-gal epitopes in clinics equipped for treating allergic reactions. Vaccinating SARS-CoV-2 α-gal binds the natural anti-Gal antibody at the vaccination site and activates the complement system to generate complement cleavage chemotactic peptides that recruit APC such as dendritic cells and macrophages.…”
Section: Covid-19 Variants As Moving Targets and How To Stop Them By Glycoengineered Whole-virus Vaccinesmentioning
confidence: 99%
“…However, the safety of virus-gal vaccines should be determined in particular in individuals with the "-gal syndrome" who are allergic to -gal epitopes in meat such as beef, pork and lamb. [91][92][93] In these individuals, bites by certain ticks in different continents (e.g., Amblyomma americanum in the USA) result in isotype switch for production of anti-Gal IgE. The binding of this IgE antibody to the multiple -gal epitopes in red meat results in an allergic immune response which appears within several hours following eating red meat.…”
Section: Virus-gal Vaccines and The -Gal Syndromementioning
confidence: 99%
“…Specifically, food allergies and chronic urticaria appear to be two of the most common differentiating cases. While differentiation with other food allergies can be easier to determine due to delay of symptom onset with AGS (Cabezas‐Cruz et al, 2019), the delayed reaction to meat can also become a confounding factor to prevent easy differentiation with chronic urticaria, not to mention that AGS and chronic urticaria can co‐exist and some even postulate a possible causal relation between the two (Pollack et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%